2018
DOI: 10.3390/f9020057
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Mass Change and Its Drivers in a Boreal Coniferous Forest in the Qilian Mountains, China from 1964 to 2013

Abstract: Carbon storage of mountain forests is vulnerable to climate change but the changes in carbon flux through time are poorly understood. Moreover, the relative contributions to carbon flux of drivers such as climate and atmospheric CO 2 still have significant uncertainties. We used the dynamic model LPJ-GUESS with climate data from twelve meteorological stations in the Qilian Mountains, China to simulate changes in carbon mass of a montane boreal forest, and the influence of temperature, precipitation, and CO 2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…This pattern is consistent with the dominant effect of water limitation on forest productivity at this precipitation level. These results are in agreement with those of other studies that found a strong positive correlation between forest AGC and precipitation (Lie et al 2018-07-12, Swetnam et al 2017, Fang et al 2018). However, plots receiving more than 1500 mm year -1 of precipitation showed a decreasing upper quantile of forest AGC, located in the middle mountains.…”
Section: Broad-scale Gradientssupporting
confidence: 93%
“…This pattern is consistent with the dominant effect of water limitation on forest productivity at this precipitation level. These results are in agreement with those of other studies that found a strong positive correlation between forest AGC and precipitation (Lie et al 2018-07-12, Swetnam et al 2017, Fang et al 2018). However, plots receiving more than 1500 mm year -1 of precipitation showed a decreasing upper quantile of forest AGC, located in the middle mountains.…”
Section: Broad-scale Gradientssupporting
confidence: 93%
“…Carbon mass of Picea crassifolia Kom. forest in the Qilian Mountains has increased by 1.202 kg/m 2 from 1964 to 2013 [ 41 ]. The correlation analysis between the change in the lower tree line position and meteorological factors showed that the change in the lower tree line was highly correlated with annual precipitation and annual average temperature; the rate of change in these two factors after 2008 has slowed down, so the elevation of decline in the lower tree line has also slowed down.…”
Section: Discussionmentioning
confidence: 99%
“…Annual evaporation is 1050–1100 mm and the annual total of sunshine hours is 1890–1900. The annual average relative humidity ranges from 60 to 65% [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Carbon mass of Picea crassifolia Kom. forest in the Qilian Mountains has increased by 1.202 kg/m 2 from 1964 to 2013 [49]. One survey showed that Picea crassifolia Kom.…”
Section: Relationship Between Tree Line Changes and Meteorological Factorsmentioning
confidence: 99%